Review dan Resetting Skema Overload Shadding Interbus Transformer 500/150 kV 1,3 Gandul dan 2 Kembangan - Ibnu Hajar; Muhammad Ridho (Energi & Kelistrikan, 2020)
Power system protection is one of the most important aspect in power system operation. Power system protection is an attempt to widely prevent the fault over the whole system. One of the power system protection schemes that have been applied by PT. PLN (Persero) to 150 kV Jawa Bali subsystem is Over Load Shedding of Interbus Transformer 500/150 kV. Over Load Shedding scheme has correctly to be set to prevent overload on secondary side of IBT 500/150 kV. Black Out occured on January 2, 2018 at 150 kV subsystem of 1,3 Gandul – 2 Kembangan – Muara Karang is one of the impact caused by incorrect-setting of Over Load Shedding scheme. The purposes of this research are to review the initial setting of Over Load Shedding scheme and to reset it as a follow-up of Black Out event occured in this subsystem. This research uses qualitative method by analyzing the overload points obtained by the simulation of DIgSILENT 14.3.1. This thesis results the new Over Load Scheme setting of IBT 500/150 kV 1 and 3 Gandul those are 3 seconds of pick-up times for the first step and 3,5 seconds of pick-up times for the second step wherein 410,98 MW is necessarily to be shed in 2 steps. Meanwhile, the new Over Load Shedding setting of IBT 500/150kV 2 Kembangan are 2 seconds of pick-up times for the first step and 2,5 seconds of pick-up times for the second step wherein 378,23 MW is necessarily to be shed in 2 steps.